Use of mechanical circulatory support in patients with non-ischemic cardiogenic shock. (3rd October 2022) - Schrage, B; Sundermeyer, J; Blankenberg, S; Graf, T; Kirchhof, P; Luedike, P; Nordbeck, P; Proudfoot, A; Orban, M; Skurk, C; Tavazzi, G; Thiele, H; et al.
Abstract: Background: The aim of this study was to evaluate mechanical circulatory support (MCS) for the treatment of non-ischemic cardiogenic shock (CS). Methods: Data from 1, 030 consecutive patients with non-ischemic CS treated with or without MCS at 16 tertiary-care centers were retrospectively collected. The association between MCS and 30-day mortality was assessed in a 1:1 propensity score matched cohort. Results: MCS was used in 406 (39%) patients. MCS treated patients presented with more severe CS (lactate 5.4 vs. 4.1 mmol/l, systolic blood pressure 80 vs. 83 mmHg, higher SCAI class) and with more disease modifiers (prior cardiac arrest 42.4 vs. 36.1%, mechanical ventilation 78.4 vs. 56.5%). After matching, 272 patients treated with were compared vs. 272 patients treated without MCS. MCS was associated with a lower 30-day mortality (hazard ratio 0.77, 95% confidence interval 0.60–0.98, Figure 1). This finding was consistent through all tested sub-groups except when ejection fraction was considered, indicating an association especially in patients with an ejection fraction ≤20%. Complications occurred more frequently in patients with MCS; e.g. severe bleedings (21.8 vs. 9.2%) and access-site related ischemia (6.6 vs. 0%). Conclusion: In patients with non-ischemic CS, MCS use was associated with lower 30-day mortality as compared to medical therapy only, particularly in patients with a lower ejection fraction. This provides rationale for randomized trials to validate these findings. Funding Acknowledgement: Type of funding sources: None.